Mechanisms of Transmission and Adaptation of tet(X4)-Positive IncHI1 Plasmids in XDR Escherichia coli from Pet Dogs: The Role of trhC, rsp, and the Tra1 Region - Pengyun Ding; Qianqian Wang; Liangliang Wang; Mengxiang Zheng; Yiming Feng; Yakun Xu; Li Yuan; Gongzheng Hu; Yushan Pan; Dandan He (Veterinary Sciences)
tet(X4)-positive IncHI1 plasmids are widely prevalent in various bacteria. To understand their transmission characteristics, we analyzed two extensively drug-resistant (XDR) Escherichia coli strains isolated from pet dog feces in Henan Province, China. Strain T28R harbored tet(X4)-positive IncHI1, IncF18:A-:B-, and mcr-1-positive IncI2 plasmids, while T16R carried tet(X4)-positive IncHI1, F16:A-:B-, and mcr-1-positive IncX4 plasmids. Four representative fusion plasmids, pT28R-F1, pT28R-F2, pT28R-F3, and pT16R-F1, in transconjugants were analyzed using WGS and PCR mapping. The results showed that IS26 from the IncF18:A-:B--plasmid attacked the conjugative transfer-associated genes trhc and rsp on the IncHI1 plasmid, generating pT28R-F1 and pT28R-F2. pT28R-F3 was generated through ISCro1- and ISCR2-mediated homologous recombination, deleting the Tra1 region of the IncHI1 plasmid. T16R-F1 emerged from ISCR2- and IS1B-mediated homologous recombination, losing transfer regions of parental plasmids. Notably, fusion plasmids lost the temperature sensitivity of the IncHI1 plasmid, with conjugation frequencies between 1.57 × 10−4 and 3.84 × 10−5 at 28 °C and 37 °C. The findings suggest that tet(X4)-positive IncHI1 plasmids could be mobilized with the assistance of conjugative helper plasmids and that fusion events enhance the adaptability of these plasmids, thus facilitating the spread of antibiotic resistance, posing a growing public health threat.